AN ARTS-BASED CURRICULUM ENCOUNTER: WHAT DOES IT MEAN TO LIVE ON THIS LAND? - Conrad, Diane; Jagger, Patricia; Bleeks, Victoria; Auger, Sarah (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
Our arts-based curriculum encounter occurred in a graduate course on arts-based research methods. For a class project we engaged in an inquiry on the question: “What does it mean to live on this land?” which we explored through various arts-based activities. The question challenged us to think deeply about our relationship with and responsibilities to the land we occupy. The inquiry raised for us and, in various ways, implicated us in issues around geographical settings, historical contexts, colonization and nationhood, relations as/with Indigenous peoples, Indigenous ways of knowing, relations with the natural environment, exploitation of the land, the environmental crisis, and our own family histories and personal journeys. In this paper, we share the reflective writings of four inquiry participants interspersed with some images from our work together.